Applications of 3D Paleontological Data at the Florida Museum of Natural History - Ziegler, Michael J.; Perez, Victor J.; Pirlo, Jeanette; Narducci, Rachel E.; Moran, Sean M.; Selba, Molly C.; Hastings, Alexander K.; Vargas-Vergara, Claudia; Antonenko, Pavlo D.; MacFadden, Bruce J. (Frontiers in Earth Science, 2020)
The past decade has seen an exponential increase of innovative applications of 3D technology in the geosciences. Here, we present a case study from the Florida Museum of Natural History applied to the multidisciplinary field of paleontology. We have deployed 3D scanning and printing techniques for the purposes of scientific research, formal education, and informal outreach. Depending on the application of the 3D file, different techniques are utilized to create high-fidelity models of physical fossil specimens or geologic field sites. These techniques include X-ray computed tomography (CT) scans, surface scans, and photogrammetry, all of which produce 3D models that vary in resolution and scale. Novel paleontological research applied non-destructive CT scanning to explore the internal anatomy of fossil museum specimens, additionally, 3D models are being used to create K–12 curricula aligned with national and state-specific education standards that are implemented in formal classroom settings. Many of these lessons are part of the NSF-funded iDigFossils project, which aims to evaluate students’ motivation and interest towards science, technology, engineering, and mathematics after participating in integrated 3D printing and paleontology lessons. Specifically, lessons on dinosaur trackways, horse evolution, and the Great American Biotic Interchange teach geologic concepts such as deep time, taphonomy, plate tectonics, and evolutionary trends. The same 3D models developed for these K–12 lessons have been used during Florida Museum’s outreach events to engage broad audiences with hands-on exhibits and activities. All 3D files are stored on open-access, online repositories, providing accessibility to fossil specimens and field sites. The application of 3D technology for the study of fossils and paleontology will continue to expand the impact of scientific discoveries for basic research as well as for broader impacts on society.